Preeclampsia and normotensive pregnancy with tribal differences in South Sulawesi: Comparison of serum interleukin-10 (IL-10) levels - Leasly Sanjoita Lamma; Muh Nasrum Massi; Sitti Wahyuni; Prihantono; Yuyun Widaningsih (Gaceta Sanitaria, 2021)
Objective: This study aims to compare the average levels of IL-10 with preeclampsia and normotensive in four different tribe populations in South Sulawesi, including Makassar, Bugis, Mandar, and Toraja. Method: This research is a cross-sectional study conducted in March–May 2020 in several Health Centre and Hospitals in four areas, namely in the UNHAS Hospital, Jumpandang Baru Health Center, Barabaraya Health Center, Mattirobulu Health Center, Salo Health Center, Lasinrang Pinrang General Hospital, Totoli Health Center, Majene Regional General Hospital, Makale Health Center, Elim General Hospital, Lakipadada Tana Toraja Regional General Hospital. Samples in this study were 88 pregnant women with gestational age >20 weeks which were divided into two groups, namely 44 cases (preeclampsia) and 44 control groups (normotensive). The criteria for the sample in this study are single pregnancy, no systemic disease, and are native Makassar, Bugis, Mandar, and Toraja tribes. Data collected included age, education, occupation, parity, Body Mass Index (BMI), history of preeclampsia. Serum IL-10 levels were examined using the Human Interleukin 10 ELISA Kit. Results: There were significant differences in IL-10 levels in preeclampsia pregnant women in the Makassar, Bugis, Mandar, and Toraja tribes (p = 0.020, p < 0.05). In contrast to the control group, there was no difference in IL-10 levels in normotensive pregnant women in the Makassar, Bugis, Mandar, and Toraja tribes (p = 0.505, p > 0.05). The Bugis, Mandar, and Toraja tribes show significant differences in IL-10 levels between preeclampsia pregnant women and normotensive pregnant women with mean rating values of pregnant women who have preeclampsia have lower IL-10 levels than normotensive pregnant women, while the Makassar tribe has valued insignificant difference in IL-10 levels between preeclampsia and normotensive (p = 0.309, p > 0.05). Conclusion: There are differences in IL-10 levels in preeclampsia pregnant women in Makassar, Bugis, Mandar, and Toraja tribes. The mean concentration of IL-10 in pregnant women with preeclampsia was significantly lower than in controls.